Job satisfaction among nurses in Hospital Sik, Kedah / Nur ‘Atikah Asari and Nur ‘Afifah Asari - Asari, Nur ‘Atikah; Asari, Nur ‘Afifah (2015)
In general, nurses in Malaysia are happy in doing their job and satisfied in everything that they do. The public satisfied with the nurses work and its help in their recovery.therefore, the purpose of this study is to know the levels of job satisfaction among nurses. Besides that, the study is to know more about the factor contributing to job satisfaction among nurses. These factors include working environment, working experience and management support. The relationship between all those factors and job satisfaction are tested in the actual study. Based on the research paper, the methods used by the researchers are pilot study, descriptive analysis, Pearson correlation and multiple regression analysis. From this findings, it shows that 63.0% of nurses agreed that they are satisfied with the nursing job. All factors influence the job satisfaction among nurses at Hospital Sik. Lastly, the most influential factors is working experience.